Agile social learning – capacity-building for sustainable development in higher education. Issue 7 (7th August 2020) - Bolmsten, Johan; Kitada, Momoko
Abstract : Purpose: The purpose of this paper is to understand the usefulness of an agile social learning method in higher education to build capacity for sustainable development at the community level. Social learning methods intend to empower students (and instructors) to work together in connection with real-life issues – combined with acquiring a conceptual understanding – to analyze issues at hand and work out solutions. The agile format of the method was aimed at a subject that is adaptive and responsive to change to empower the students to take action toward sustainable development. Design/methodology/approach: This study was based on a case study methodology where the running of the subject was documented and analyzed for two years. The target student group was maritime professionals who had an interest or were in a position to work with developing sustainable solutions in their home organizations (mostly in developing countries). Findings: The results of the analysis indicate how the students learned about environmental, social and economic spheres of sustainable development and their linkages; how the subject format stimulated the students to develop different "learning paths" between the three spheres of sustainable development, which enabled a multi-faceted understanding of sustainable development issues; and, finally, how the students were able to design evolvable sustainable development solutions. Originality/value: The results indicate both the novelty and usefulness of the agile social learning method to build capacity for sustainable development through the subject designed for higher education.